الإيمان والعبادة بيـن الوحدة الفطرية والتعددية التصويرية: رؤية أكبرية: Faith and Worship Between Innate Unity and Imaginal Plurality: An Akbarian Perspective - Mohammed دين محمد محمد ميرا صاحب (الدراسات الإسلامية, 2024)
With growing interest in interfaith dialogue, the search for unity within diversity has become a focal point of religious thought and hermeneutics. It is increasingly common to hear that all religions essentially preach the same truth, echoing John Hick’s assertion that “Allah Almighty Has Many Names.” While all religions claim belief in one God as the ultimate reality, their diverse worship practices and theological expressions often appear contradictory. Addressing this issue requires collective theological deliberation by scholars of all religions. However, examining perspectives within individual faith systems can also be beneficial. Muḥyi al-Dīn Ibn ʻArabī (d. 1240) offers a valuable perspective for this global discussion. Rooted in Islamic sources, Ibn ʻArabī introduces the hermeneutical principle of “one Allah Almighty and diverse forms of representation.” He asserts that, regardless of the form of worship, it is ultimately Allah who is being worshipped, even if the worshipper is unaware of it. This principle aligns with the Qur’anic declaration that Allah’s creatures will worship none but Him and resonates with the innate human recognition of Allah’s oneness. This paper aims to explain Ibn Arabi’s perception of accessible language, hoping to aid those discussing the complex theme of “unity within diversity”.